Vacuolar Processing Enzymes Modulating Susceptibility Response to Fusarium oxysporum f. sp. cubense Tropical Race 4 Infections in Banana - Wan Abdullah, Wan Muhamad Asrul Nizam; Saidi, Noor Baity; Yusof, Mohd Termizi; Wee, Chien-Yeong; Loh, Hwei-San; Ong-Abdullah, Janna; Lai, Kok-Song (Frontiers in Plant Science, 2022)
Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) is a destructive necrotrophic fungal pathogen afflicting global banana production. Infection process involves the activation of programmed cell death (PCD). In this study, seven Musa acuminata vacuolar processing enzyme (MaVPE1–MaVPE7) genes associated with PCD were successfully identified. Phylogenetic analysis and tissue-specific expression categorized these MaVPEs into the seed and vegetative types. FocTR4 infection induced the majority of MaVPE expressions in the susceptible cultivar “Berangan” as compared to the resistant cultivar “Jari Buaya.” Consistently, upon FocTR4 infection, high caspase-1 activity was detected in the susceptible cultivar, while low level of caspase-1 activity was recorded in the resistant cultivar. Furthermore, inhibition of MaVPE activities via caspase-1 inhibitor in the susceptible cultivar reduced tonoplast rupture, decreased lesion formation, and enhanced stress tolerance against FocTR4 infection. Additionally, the Arabidopsis VPE-null mutant exhibited higher tolerance to FocTR4 infection, indicated by reduced sporulation rate, low levels of H2O2 content, and high levels of cell viability. Comparative proteomic profiling analysis revealed increase in the abundance of cysteine proteinase in the inoculated susceptible cultivar, as opposed to cysteine proteinase inhibitors in the resistant cultivar. In conclusion, the increase in vacuolar processing enzyme (VPE)-mediated PCD played a crucial role in modulating susceptibility response during compatible interaction, which facilitated FocTR4 colonization in the host.